2022
DOI: 10.3390/atmos13050810
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine Affects Multiple Biological Processes in EpiDermTM Organotypic Tissues and Keratinocyte Monolayers

Abstract: Dermal exposure to nicotine is common due to the widespread use of tobacco products. Here, we assessed the effects of nicotine at concentrations found in thirdhand smoke (THS) contaminated environments and electronic cigarette (EC) spills or leaks on a 3D human skin model (EpiDermTM) and on submerged keratinocyte cultures. Air liquid interface treatment of EpiDermTM with 10 or 400 μg/mL of nicotine for 24 h followed by proteomics analysis showed altered pathways related to inflammation, protein synthesis, cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…A study by Pozuelos et al examined the effect of nicotine on both keratinocyte cultures and a 3D model of human skin (EpiDermTM). The results showed that nicotine damages cellular organs, disrupts the homeostasis of reactive oxygen species, and causes oxidative damage to skin cells [ 25 ]. Likewise, Lee and colleagues examined the effects of nicotine on immortalized and malignant keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Pozuelos et al examined the effect of nicotine on both keratinocyte cultures and a 3D model of human skin (EpiDermTM). The results showed that nicotine damages cellular organs, disrupts the homeostasis of reactive oxygen species, and causes oxidative damage to skin cells [ 25 ]. Likewise, Lee and colleagues examined the effects of nicotine on immortalized and malignant keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Our EC participants used second generation products that can operate at high powers, which may have generated aerosols that were more toxic than those produced by low powered fourth generation ECs. However, fourth generation products, such as JUUL TM , contain high concentrations of nicotine (~60 mg/mL) [ 70 , 71 ], flavor chemicals, and coolants [ 72 ] that could affect gene expression and/or protein levels, as shown in other tissues [ 51 , 73 , 74 ] and may produce results that differ from the current study. A greater number of DEGs were identified in the EC vs. NS set than in the CS vs. NS and CS vs. EC sets, similar to several previous studies [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 83%
“…Cellular morphology is a crucial aspect of cytotoxic evaluations, which involve assessing the toxic effects of various substances on living cells. Cellular morphology refers to the physical structure and shape of cells, and it plays a significant role in understanding the impact of cytotoxic agents [30]. Nicotine derived from electronic cigarettes induced a profound and concentration-dependent alteration in the morphology of human keratinocytes.…”
Section: Resultsmentioning
confidence: 99%